Mood repair in healthy individuals: Both processing mode and imagery content matter. (March 2016) - Seebauer, Laura; Arthen, Tobias; Austermann, Marit; Falck, Johannes; Koch, Lennart; Moulds, Michelle L.; Jacob, Gitta A.
Abstract: Background: The recall of positive autobiographical memories (mood repair) is an effective strategy for improving sad mood. In depressed individuals mood repair has shown to be most effective, if the memory was processed in a concrete (imaginable), as opposed to an abstract (verbal) processing mode. However, it is not yet clear whether this also applies to healthy subjects. Moreover we do not know whether intensity and content of an imagery stimulus influences its effectiveness. We report on two experimental studies in healthy participants. Methods: Negative emotion induction was followed by mood repair via recall of positive autobiographical memories. In study I, abstract processing was compared to two concrete processing strategies (high concrete/low concrete). In study II, the content of the memories was systematically varied (social/achievement). Results: In study I, a concrete processing resulted in better mood repair, however no differences were found between high and low concrete processing. In study II, both types of memories had comparable effects on mood repair but promoted different emotions. Limitations: Only a young, healthy, predominantly female population was investigated. Conclusions: Adopting a concrete processing mode when recalling positive memories leads to better mood repair in healthy participants. Moreover, the content of the memory determines the corresponding emotions. Highlights: Sad mood induction via film clips, followed by positive memory recall (mood repair). Concrete processing of positive memory was more effective than abstract processing. High concrete processing was as effective as low concrete processing. Social memories and memories of achievements were equally effective. Specific memories were suitable to induce specific positive emotions (love/pride).